Pushing the limits of electrochemistry toward challenging applications in clinical diagnosis, prognosis, and therapeutic action. Issue 18 (28th January 2019) - Yáñez-Sedeño, P.; Campuzano, S.; Pingarrón, J. M.
Abstract : Key aspects, current trends, and future perspectives with respect to electrochemical affinity biosensors for clinical diagnosis, prognosis, and therapeutic actions are discussed. Abstract : Constant progress in the identification of biomarkers at different molecular levels in samples of different natures, and the need to conduct routine analyses, even in limited-resource settings involving simple and short protocols, are examples of the growing current clinical demands not satisfied by conventional available techniques. In this context, the unique features offered by electrochemical biosensors, including affordability, real-time and reagentless monitoring, simple handling and portability, and versatility, make them especially interesting for adaptation to the increasingly challenging requirements of current clinical and point-of-care (POC) diagnostics. This has allowed the continuous development of strategies with improved performance in the clinical field that were unthinkable just a few years ago. After a brief introduction to the types and characteristics of clinically relevant biomarkers/samples, requirements for their analysis, and currently available methodologies, this review article provides a critical discussion of the most important developments and relevant applications involving electrochemical biosensors reported in the last five years in response to the demands of current diagnostic, prognostic, and therapeutic actions related to high prevalence and high mortality diseases and disorders. Special attention is paid to the rational design of surface chemistry and the use/modification of state-of-the-art nanomaterials to construct electrochemical bioscaffolds with antifouling properties that can be applied to the single or multiplex determination of biomarkers of accepted or emerging clinical relevance in particularly complex clinical samples, such as undiluted liquid biopsies, whole cells, and paraffin-embedded tissues, which have scarcely been explored using conventional techniques or electrochemical biosensing. Key points guiding future development, challenges to be addressed to further push the limits of electrochemical biosensors towards new challenging applications, and their introduction to the market are also discussed.